Dynamic transcriptional profiling provides insights into tuberous root development in Rehmannia glutinosa - Sun, Peng; Xiao, Xingguo; Duan, Liusheng; Guo, Yuhai; Qi, Jianjun; Liao, Dengqun; Zhao, Chunli; Liu, Yan; Zhou, Lili; Li, Xianen (Frontiers in Plant Science, 2015)
Rehmannia glutinosa, a herb of the Scrophulariaceae family, is widely cultivated in the Northern part of China. The tuberous root has well known medicinal properties; however, yield and quality are threatened by abiotic and biotic stresses. Understanding the molecular process of tuberous root development may help identify novel targets for its control. In the present study, we used Illumina sequencing and de novo assembly strategies to obtain a reference transcriptome that is relevant to tuberous root development. We then conducted RNA-seq quantification analysis to determine gene expression profiles of the adventitious root (AR), thickening adventitious root (TAR), and the developing tuberous root (DTR). Expression profiling identified a total of 6,974 differentially expressed unigenes during root developmental. Bioinformatics analysis and gene expression profiling revealed changes in phenylpropanoid biosynthesis, starch and sucrose metabolism, and plant hormone biosynthesis during root development. Moreover, we identified and allocated putative functions to the genes involved in tuberous root development, including genes related to major carbohydrate metabolism, hormone metabolism, and transcription regulation. The present study provides the initial description of gene expression profiles of AR, TAR, and DTR, which facilitates identification of genes of interest. Moreover, our work provides insights into the molecular mechanisms underlying tuberous root development and may assist in the design and development of improved breeding schemes for different R. glutinosa varieties through genetic manipulation.